2020
DOI: 10.1002/slct.201904648
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of BiOCl/ZnO/CN Nanocomposite for Visible‐Light Photocatalytic Degradation of Dyes

Abstract: The zinc oxide (ZnO) based heterogeneous semiconductors has acknowledged extensive attention but its property was radically repressed because of diminutive visible light photocatalytic activity. Herein, metal-nonmetal hetero-structure coupling is adopted to encompass the visible light harvesting capability and endorses the charge separation and transferring efficiency. Graphitic-carbon-nitride (CN) and bismuth oxychloride (BiOCl) semiconductors were effectively incorporated into the ZnO crystal structure by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In contrast, the narrow bandgap of BiOI possesses poor redox potential [6] . To overcome these drawbacks, various strategies have been approached, such as heterojunction construction, [7] and aliovalent doping [8] . Solid solution formation is another easy way to tune the band edge position toward a suitable bandgap value within adequate redox potentials for reduction and oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the narrow bandgap of BiOI possesses poor redox potential [6] . To overcome these drawbacks, various strategies have been approached, such as heterojunction construction, [7] and aliovalent doping [8] . Solid solution formation is another easy way to tune the band edge position toward a suitable bandgap value within adequate redox potentials for reduction and oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Similarly, Zhang et al have demonstrated that BiOCl/ZnO/C 3 N 4 photocatalyst exhibited superior photodegradation performance for RhB and methyl orange (MO) to BiOCl/ZnO, BiOCl and C 3 N 4 . 31 Additionally, Liu et al have prepared BiOCl/ZnO heterostructures with oxygen-rich vacancies using a one-step microwave technique, which can effectively enhance photocatalytic performance for the degradation of tetracycline hydrochloride (TC-HCl) than those of pure BiOCl and ZnO. This study showed that oxygen vacancy and interfacial electric field derived from heterostructures were responsible for the improvement of light harvesting and the separation efficiency of photogenerated charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Finding solutions to water pollution as soon as possible is a necessary condition for the further development of society. As a representative of green chemistry, photocatalysis has the advantages of simple operation, green pollution‐free, and fast degradation rate in the degradation of water pollutants [1–7] . In particular, it can completely degrade organic pollutants into harmless H 2 O and CO 2 , and will not cause secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative of green chemistry, photocatalysis has the advantages of simple operation, green pollution-free, and fast degradation rate in the degradation of water pollutants. [1][2][3][4][5][6][7] In particular, it can completely degrade organic pollutants into harmless H 2 O and CO 2 , and will not cause secondary pollution. Bismuth oxyiodides (BiOI), as a typical main group V-VI-VII ternary semiconductors with layered crystal structures, [8] the unit cell consists of 6 atoms (2 O, 2 Bi, 2 I), a Bi atom coordinates with the surrounding 4 O atoms and 4 I atoms to form an decahedral asymmetrical cone structure.…”
Section: Introductionmentioning
confidence: 99%